The promise and pitfalls of mass drug administration to control intestinal helminth infections - Humphries, D.; Nguyen, S.; Boakye, D.; Wilson, M.; Cappello, M. (Current Opinion in Infectious Diseases, 2012)
Purpose of Review: Intestinal helminth infections continue to cause significant morbidity in resource-limited settings. Recent efforts at global control have centered on mass drug administration (MDA) of praziquantel and benzimidazole anthelminthics to reduce the prevalence and intensity of schistosomiasis and soil-transmitted nematode infections, respectively. This review summarizes progress and potential challenges associated with MDA. Recent Findings: Data from studies conducted in endemic areas show that chemotherapeutic interventions can reduce prevalence and intensity of infection with intestinal helminths, and have the potential to reduce transmission within populations. However, consistent benefits in high-risk groups, including children and pregnant women, have not been established. The long-term benefits of MDA remain to be determined, and the potential for emerging resistance to impact effectiveness have not yet been defined. CONCLUSIONS: Whereas studies evaluating MDA have shown benefit in certain populations, intensive monitoring and evaluation, as well as a commitment of resources for new drug development, are essential for long-term control or elimination of intestinal helminth infections. © 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Keywords: benzimidazoles; mass drug administration; praziquantel; schistosomiasis; soil-transmitted nematodes